2022
DOI: 10.7150/ijbs.65044
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models of nonalcoholic fatty liver disease (NAFLD): pathomechanisms and pharmacotherapies

Abstract: The prevalence of non-alcoholic fatty liver disease (NAFLD) increases year by year, and as a consequence, NAFLD has become one of the most prevalent liver diseases worldwide. Unfortunately, no pharmacotherapies for NAFLD have been approved by the United States Food and Drug Administration despite promising pre-clinical benefits; this situation highlights the urgent need to explore new therapeutic targets for NAFLD and for the discovery of effective therapeutic drugs. The mouse is one of the most commonly used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 190 publications
0
15
0
Order By: Relevance
“…Based on previous studies, there is no unified method for establishing MAFLD mouse models 34 , 35 . In many studies, ApoE -/- mice were fed with HFD at approximately 8-12 weeks 36 , 37 . All MAFLD mouse models were testified by Oil red O staining and other metabolic-associated tests to prove successful modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, there is no unified method for establishing MAFLD mouse models 34 , 35 . In many studies, ApoE -/- mice were fed with HFD at approximately 8-12 weeks 36 , 37 . All MAFLD mouse models were testified by Oil red O staining and other metabolic-associated tests to prove successful modeling.…”
Section: Discussionmentioning
confidence: 99%
“…The I-WD mice exhibited an increase in the glucose tolerance test curve, highlighting the development of glucose intolerance, and an increase in total cholesterol, LDL, HDL, and TG levels, indicating dyslipidemia [ 36 ]. In the liver, the I-WD mice exhibited hepatomegaly development, significant steatosis associated with hepatocyte ballooning, and type 3 collagen gene expression, which are distinctive of NAFLD development [ 35 , 37 ]. This pattern of repetitive weight loss and regain associated with the development of metabolic complications is characteristic of weight cycling [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…This increase in necroptosis was associated with an increase in markers of inflammation in the liver. Because inflammation plays a role in chronic liver disease [ 35 ] and chronic liver disease increases with age, we measured the impact of overexpressing either Ripk3 or Mlkl on steatosis and fibrosis in the old mice. We found that the age-related increase steatosis and fibrosis was significantly increased in the old hRipk 3-KI and hMlkl -KI mice.…”
Section: Discussionmentioning
confidence: 99%